PROSPEK PENGEMBANGAN KACANG TANAH UNTUK MENUNJANG KETAHANAN PANGAN: (STUDI KASUS UJI VARIETAS DI DESA MAKAMENGGIT KABUPATEN SUMBA TIMUR – NTT) - Widiyono, Wahyu (Jurnal Rekayasa Lingkungan)
To understand the prospect of groundnut development (Arachis hypogaea) for supporting food security in semi arid area, survey and experiment of groundnut varieties were undertaken in Makamenggit Village, East Sumba District, the East Nusa Tenggara Province. Aim of research was to understand natural resources (soil, climate and water) and production potency based on cased study of 6 (six) varieties of groundnut which was cultivated under manure treatment. The six groundnut varieties, i.e. Tupai, Komodo, Zebra, Gajah, Bogor variety and Makamenggit local variety were cultivated in vertisol soil type, organic manure of buffalo feces, irrigation manually from water river in dry season. Parameters of plant height, leave number, and leave cover each individual plant were observed every week, since 5 weeks until 12 weeks after planting. Survey indicated that agro-climate and hydrology of East Sumba was very potential to support groundnut development not only in the rainy season short period (3-4 months), but also in the dry season by utilization of the existence of waterresources (some river and ‘embung-embung’). Result of research showed that six varieties of groundnut had good vegetative growth. The Makamenggit local variety which showed vegetative growth so good performance was potential to promote as a national superior seed. It was obviously that organic manure could increase groundnut vegetative growth (and also reproductive yield) at the vertisol soil type. To develop groundnut cultivation in East Sumba area the utilization of organic manure, cultivation in dry season by irrigation of limited water and seed diversity need to be socialized continuously to the farmers.Keywords: natural resources, prospect, groundnut, food security, east Sumba.